2022
DOI: 10.1108/sasbe-12-2021-0224
|View full text |Cite
|
Sign up to set email alerts
|

Toward digital construction supply chain-based Industry 4.0 solutions: scientometric-thematic analysis

Abstract: PurposeThe wood construction industry has been described as slow in adapting efficiency-increasing activities in its operations and supply chain. The industry is still facing challenges related to digitalization, such as fragmentation, poor traceability and lack of real-time information. This study evaluates the status of digitalization in construction supply chains by thematically analyzing the existing literature and mapping research trends.Design/methodology/approachA review of the key literature from 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 77 publications
(219 reference statements)
0
16
0
Order By: Relevance
“…The examination of the identified barriers compared with the results of the literature review revealed many similarities. Barriers related to resources and cost (G2) [36,49,55,62,63], skills and knowledge (G3) [9,21,29,31], human behaviour (G5) [44,49,55], and governmental (G7) [21,31,49] were all identified previously from similar studies in the literature review, as shown in Table 1. Other barriers were mentioned by participants and were found to be related to the wood industry in particular, such as interoperability issues [46,64] and insufficient object libraries (G1) [50].…”
Section: Comparison Between Gt Results and Literature Review Resultsmentioning
confidence: 88%
“…The examination of the identified barriers compared with the results of the literature review revealed many similarities. Barriers related to resources and cost (G2) [36,49,55,62,63], skills and knowledge (G3) [9,21,29,31], human behaviour (G5) [44,49,55], and governmental (G7) [21,31,49] were all identified previously from similar studies in the literature review, as shown in Table 1. Other barriers were mentioned by participants and were found to be related to the wood industry in particular, such as interoperability issues [46,64] and insufficient object libraries (G1) [50].…”
Section: Comparison Between Gt Results and Literature Review Resultsmentioning
confidence: 88%
“…They managed the supply chain tasks, including purchasing, carrying and inventory tasks using blockchain smart contracts to speed the processing of plastic waste. Integrating products and services in an interconnected process using blockchain can enable to estimation the product lifecycle (Gharaibeh et al , 2022; Kouhizadeh et al , 2019; Vogel et al , 2019). Reserve logistics (RL) is a vital dimension in the CE process; therefore, Bekrar et al (2021) proposed a nexus of transportation, RL and blockchain to digitize the operation of the transportation equipment reserve supply chain.…”
Section: Circular Economy and Emerging Digital Technologiesmentioning
confidence: 99%
“…The article [2] is the opposite of the first -it is cited twice, published in 2022, and its title can be interpreted as the relevant issue of Digital Industry: "Toward digital construction supply chain-based Industry 4.0 solutions: scientometric-thematic analysis". Supply chain-based Industry 4.0 solutions are an obvious issue, just think of the challenges in logistics during the pandemic and the sanctions; the digitalization of logistics is necessary to quickly adapt solutions in a fast-changing environment.…”
Section: Introductionmentioning
confidence: 99%